Relationship between the Social Capability and the Social Performance of Brazilian Companies Mediated by Corporate Social Responsibility - Leão de Miranda, Ronaldo; Regina dos Santos Parisotto, Iara (Advances in Scientific and Applied Accounting, 2023)
Objective: This study aims to analyze the relationship between the social capability and the social performance, mediated by corporate social responsibility, in the context of Brazilian companies listed on B3. Method: The research is characterized as descriptive in terms of its objective, and as applied research in terms of procedures, based on primary data collection. This study was conducted with publicly traded companies in Brazil, through the administration of a questionnaire to the managers of the companies listed on B3. The questionnaire responses were obtained from top management. It is quantitative research in relation to the problem approach, analyzed through structural equation modeling (SEM) using SPSS AMOS version 22 software. Results: The importance of social capability is not just a strategic consideration for achieving good social performance and CSR results; it is, above all, a primary and fundamental consideration when it comes to achieving the social objectives of companies. Therefore, this study proves that there is a relationship between the social capability and the social performance of Brazilian companies mediated by corporate social responsibility. This mediation path SC => CSR => SP has a ß= 0.705, where SC and CSR explain the SP by approximately 93%. Contributions: The study contributes by clarifying, in the mediation test, that the corporate social responsibility positively mediates the relationship between the social capability and the social performance of Brazilian companies. Simply involving stakeholders in decision-making processes and including their needs in the definition and implementation of organizational social objectives is not sufficient to meet the interests of stakeholders. As a practical implication, the empirical research evidence can contribute to elucidating discussions about social capability assisting managers and directors of Brazilian companies in better understanding their role in the distribution of non-financial goods.